2019
DOI: 10.1007/s10008-019-04323-4
|View full text |Cite
|
Sign up to set email alerts
|

The computational methods in the development of a novel multianalyte calibration technique for potentiometric integrated sensors systems

Abstract: In recent years, integration and miniaturization of ion-selective electrodes (ISEs) have brought many benefits resulting in the possibility of simultaneous determination of the ions concentration in small volume samples. One of the key problems related to the preparation of potentiometric integrated sensors systems (PISSs) is a calibration procedure due to the necessity to calibrate each particular sensor separately. The main aim of the research was to develop a novel calibration method for PISSs fabricated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…Detailed data can be found in Table 2. Long-term stability corresponded with our previous research described in Urbanowicz et al's work [63].…”
Section: Parameters Of Multisensor Platformssupporting
confidence: 91%
See 1 more Smart Citation
“…Detailed data can be found in Table 2. Long-term stability corresponded with our previous research described in Urbanowicz et al's work [63].…”
Section: Parameters Of Multisensor Platformssupporting
confidence: 91%
“…This paper presents the results of the research carried out using the miniature multisensor platform of own construction composed of solid-contact ion-selective electrodes. This work is a continuation of study on the use of miniature ISEs in biomedical research [63]. Our previous article focused on examining some factors influencing ISE response, including lifetime parameters, and also showed the algorithm that allows designing ionic composition of solutions for calibration of MP-ISEs.…”
Section: Introductionmentioning
confidence: 94%
“…Recently Urbanowicz et al [ 41 ], reported on a very small multiple biosensing platform of 10 mm diameter, relying on solid contact ion-selective electrodes for the detection of electrolytes Na + , K + , Ca 2+ , Mg 2+ , and Cl − in fresh human saliva samples. This electrolyte evaluation is essential to manage the progression of a number of non-communicable diseases, such as type-2 diabetes mellitus and lipid profile [ 42 ].…”
Section: Electrochemical Methods Employed On Disease Diagnosismentioning
confidence: 99%
“…The overall diameter of the Au-ISE with case was 2 mm and the GC-ISE 6 mm. Detailed description of the construction is given in our previous reports [68][69][70].…”
Section: Equipmentmentioning
confidence: 99%